AN ANALYSIS OF RACHEL BERRY’S CHARACTER IN GLEE SEASON 2 USING MASLOW’S THE HIERARCHY OF NEEDS THEORY - Nurhajar, Ayu Sukma; Sunggingwati, Dyah; Valiantien, Nita Maya (Fakultas Ilmu Budaya Universitas Mulawarman, 2018)
ABSTRACT Literary work today is not limited by written form such as novel and short story. Film can be considered as literary work as well due to its narrative device. Glee is an American series which takes social issues in each episode. This study is intended to analyse Rachel Berry’s character based on how she satisfies the hierarchy of needs and to show the characteristics of self-actualized person that she exhibits. The data of this study are taken from the dialogues and narrations from the series. This study uses Maslow’s the hierarchy of needs theory. The data are analysed using qualitative descriptive method. The results of this study show that Rachel Berry is a self-actualizer. Rachel Berry has satisfied the four lower level of needs (physiological needs, safety and security needs, love and belongingness needs, and esteem needs) before she reaches the pinnacle of the hierarchy of needs. Rachel Berry shows some characteristics of self-actualizer, which include an acceptance of her strengths and weaknesses, depends on herself for her satisfaction, has moments of peak experiences, has sympathy and empathy as well as is willing to help others, tends to select friends with similar quality as her own and has creativeness. Keywords: Glee, character, the Hierarchy of Needs Theory, self-actualization, self-actualized person ABSTRAK Karya sastra hari ini tidak terbatas pada karya tertulis seperti novel atau cerita pendek. Film termasuk dalam karya sastra mengacu pada narasi yang digunakan. Glee adalah serial Amerika yang mengangkat isu-isu sosial pada setiap episodenya. Penelitian ini bertujuan untuk menganalisa karakter Rachel Berry tentang bagaimana dia memenuhi segala kebutuhan dalam hierarki dan menunjukkan karakteristik dari seorang pengaktualisasi diri. Data-data diambil dari dialog dan narasi dalam serial Glee dan kemudian dianalisa menggunakan metode kualitatif deskriptif. Penelitian ini menggunakan teori hierarki kebutuhan Maslow. Hasil penelitian menunjukkan bahwa Rachel Berry adalah seorang pengaktualisasi diri. Rachel telah memenuhi empat kebutuhan tingkat bawah dalam hierarki ( kebutuhan fisiologi, kebutuhan akan rasa aman, kebutuhan akan rasa memiliki dan kasih sayang, kebutuhan akan penghargaan) sebelum dia mencapai kebutuhan puncak dalam hierarki. Rachel Berry menunjukkan beberapa karakteristik seorang pengaktualisasi diri, yaitu menerima kelebihan dan kekurangan dirinya, bergantung pada dirinya sendiri, memiliki saat-saat peak-experiences, memiliki simpati dan empati serta kemauan untuk menolong orang lain, cenderung memilih teman yang memiliki kualitas yang sama dengan dirinya, dan memiliki kreativitas. Kata kunci: Glee, karakter, teori hierarki kebutuhan Maslow, aktualisasi-diri